Product development: e-ta'awun PA takaful+ / Mohd Faizan Mohd Afandi ... [et al.] - Mohd Afandi, Mohd Faizan; Shamsuddin, Norazrisham; Zubairi, Muhamad Izmul Nizam; Mohammad Hatta, Mohammad Firdaus; Jaafar, Mohamad Nizam (2021)
Takaful has rapid growth as an industry that has great potential in Malaysian and the global markets. Takaful is a modern and innovative approach to manage the demand for a shariah compliant instrument that can mitigate an individual's exposure to specific types of risk. It is largely due to the shariah principles that emphasize the value of mutual help and shared responsibility with the elimination of shariah prohibited elements such as interest, excessive uncertainty, and gambling in its business operation. The introduction of the Islamic Finance Service Act (IFSA) 2013 has opened a new chapter in the Takaful industry in Malaysia, starting with the segregation of Family Takaful and General Takaful that have provided an opportunity for the Takaful operators to focus on expanding their business to compete or at least be at par with the conventional insurance in the market. One of the famous Takaful products under General Takaful is personal accident protection. In this study, digitalization is an important element to be highlighted by the researchers. Realizing the importance of financial technology (Fintech) in Takaful management, some modifications and innovations have been done to cater for the demand from the Takaful market. A new personal accident product namely e-Ta'awun PA Takaful+ has been developed to provide the potential customers with conveniences and accessible to the Takaful product.